Inconvenient dialogues at the Jaburu Palace: the mediatisation of political scandal in the Jornal Nacional - Fernandes, Carla Montuori; De Oliveira, Luiz Ademir; Correia Chagas, Genira [UNESP] (Centro Int Estudios Superiores Comunicacion Amer Latina-ciespal, 2021)
This essay discusses the relation between knowledge, comprehension and culture, identifies the epistemological and intersubjective roots in the notion of comprehension and stresses some of the bonds between the studies on culture and comprehension as a method. Based on Montaigne's, Medina's, Morin's and others' critique of the fragmentation of scientific knowledge, the paper charts the path treaded by several authors who have contributed for the concept of comprehension as a method to link, unite, gather lore and knowledge. In dialogue with scholars of several fields, i.e. Arendt, Buber, Campbell, Weber, Popper, Latour and Bakhtin, we present the dialog between different practices of knowledge as a way for knowing, communicating and participating in cultures.
Keywords: political scandal; political communication; television journalism; jornal nacional